2011
DOI: 10.1016/j.psyneuen.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cortisol on emotional responses depends on order of cortisol and placebo administration in a within-subject design

Abstract: Cortisol does not exhibit a straightforward relationship with mood states; administration of glucocorticoids to human subjects has produced mixed effects on mood and emotional processing. In this study, participants (N=46) received intravenous hydrocortisone (synthetic cortisol; 0.1 mg/kg body weight) and placebo in randomized order over two sessions 48 hours apart. Following the infusion, participants rated neutral and unpleasant pictures. In Session 1, participants reported elevated negative affect (NA) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 57 publications
(95 reference statements)
2
43
0
Order By: Relevance
“…Participants were screened for inclusion in the study by phone. For logistical reasons unrelated to the present hypotheses, men and women using HBC were included (Kirschbaum et al, 1999; Wirth et al, 2011). The majority (60%) of women were using a monophasic progestin/estrogen (e.g., Yasmin) while the remaining women were taking a triphasic progestin/estrogen (e.g., Ortho Tri-Cyclen).…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were screened for inclusion in the study by phone. For logistical reasons unrelated to the present hypotheses, men and women using HBC were included (Kirschbaum et al, 1999; Wirth et al, 2011). The majority (60%) of women were using a monophasic progestin/estrogen (e.g., Yasmin) while the remaining women were taking a triphasic progestin/estrogen (e.g., Ortho Tri-Cyclen).…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…All study sessions were scheduled so that neither drug administration session fell within the HBC “placebo” week. Exclusion and inclusion criteria are described in more detail in Wirth et al (2011). Fifty-four participants were enrolled in the study.…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research on the effects of exogenous cortisol suggests that relations between cortisol and negative emotions are dependent on situational factors, including the novelty of the experimental environment and task familiarity [6]. Studies have also found that elevated levels of cortisol may improve accuracy on emotional memory tasks [7,8].…”
mentioning
confidence: 99%